Technological gap and heterogeneous oligopoly - Huang, Weihong (2019)
This paper explores the effect of technological gap on output, profits, market concentration, and social welfare in quantity setting oligopoly with firms of unequal sizes, holding different conjectures, operating with non-identical costs, and producing homogenous products. Assuming firms with relatively advanced technology adopt sophisticated Cournot strategy while the remaining with backward technology behave as price takers, we find that an increase in technological gap between two types of firms may paradoxically lead to higher profits for not only the advanced but also the backward. Moreover, wider technological distance could lead to lower market concentration and be welfare enhancing.